Towards an Evidence-Based Approach to Pre-trial Detention in Europe - Martufi, Adriano (European journal on criminal policy and research, 2022)
This editorial seeks to introduce the special issue Towards an Evidence-Based Approach to Pre-trial Detention in Europe. It explains the state of the field surrounding the legal practice of pre-trial detention and why an interdisciplinary approach is warranted. Pre-trial detention is an instrument in criminal procedure that has been reportedly overused in several European systems, but the reasons remain partly unexplored. While legal scholarship continues to focus predominantly on the legal framework, more disciplines are involved in the way this applies in practice. This special issue gathers contributions from political scientists, (forensic) psychologists, criminologists and jurists who approach this phenomenon from different angles and therefore provide a deeper and more evidence-based understanding of how its practice operates. The special issue is structured along four themes highlighting the trends in scholarship regarding pre-trial detention, namely decision-making, risk-prediction, legal culture, and harmonisation. The editorial elucidates the narrative of the special issue and briefly presents the key points of each contribution.